Local Wisdom Value of Anak Dalam Tribe Jambi in Agricultural Field as A Learning Source of Biology - Lia Yosephin Sinaga; Nuryani Y. Rustaman (Universitas Sebelas Maret, 2015)
Education nowadays more emphasizes a nation character and value. Nation character and value is the accumulation of local character and value from indigenous in Indonesia. The local tradition has wisdom value. The apllication of nation character and value requires teachers to be wise in choosing the right learning resources to the character of the students with regard to the character and local area. Based on those research background, one of many ways developing student character is exploring local wisdom and implementing as a lesson source. This research aims to reveal local wisdom values from Anak Dalam tribe tradition in Jambi province conducted in group vice tumenggung Bajeloin the village of Bukit Suban, Sarolangun, Jambi toward the cultivation and then implemented as a learning resource biology. This research was conducted by in-depth interviews, participant observation, documentation studies, and field notes were analyzed by triangulation techniques, with data collection, data reduction, and data display. Activities undertaken in the agricultural fields was mancah (slashing), matiko ukor (lethal root), nobong (overthrow), ngengong totobongon (drying), bekor (burning), menugal (puncture), maintenance and weeding. Based on the identification of farming activities, it is founded that values of local wisdom relating to environmental protection, such as: the value of harmony, balance value, the value of environmental conservation, sustainable values, and the values of mutual cooperation. These values are implemented as a biological learning resource which derived from the competences standard of analyze the utilization and conservation of the environment.Keywords: Local Wisdom Value, Suku Anak Dalam Jambi, Source Of Biology Learning